Paid Maternity Leave and Female Employment : Evidence Using Firm-Level Survey Data for Developing Countries - Amin, Mohammad; Islam, Asif (World Bank, Washington, DC, 2019)
The relationship between the length of paid maternity leave and the proportion of female workers in the private sector is explored using firm-level survey data for 66 mostly developing countries. The paper finds a large, positive, and statistically significant relationship between the two. According to the most conservative estimate, an increase of one week of paid maternity leave is associated with a 2.6 percentage points increase in the share of workers in a typical firm that are female. As expected, the stated relationship is much larger when the government pays for maternity leave versus the employer. The results are robust to several controls for firm and country characteristics and other possible heterogeneities in the maternity leave and female workers relationship.